1-Benzoyl-3,3-dibutylthiourea - Gunasekaran, N.; Karvembu, R.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title molecule, C(16)H(24)N(2)OS, is twisted about the central N(H)-C bond with a C-N(H)-C-N torsion angle of -62.67 (15)degrees. The carbonyl group is twisted out of the plane of the benzene ring, forming a C-C-C=O torsion angle of -25.06 (17)degrees. In the crystal, molecules related by centres of symmetry are linked by pairs of intermolecular N-H center dot center dot center dot S hydrogen bonds, forming eight-membered {center dot center dot center dot HNCS}(2) synthons. These are further connected by weak via C-H center dot center dot center dot O contacts, forming a two-dimensional array in the bc plane.